HUBUNGAN DUKUNGAN SUAMI DENGAN BREASTFEEDING SELF EFFICACY DALAM PEMBERIAN ASI DI WILAYAH KERJA PUSKESMAS BANDA RAYA KOTA BANDA ACEH: HUBUNGAN DUKUNGAN SUAMI DENGAN BREASTFEEDING SELF EFFICACY DALAM PEMBERIAN ASI DI WILAYAH KERJA PUSKESMAS BANDA RAYA KOTA BANDA ACEH - Aida Fitri; Syahral Helfiva; Syifa Az-zahra; Elka Halifah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2022)
Self-efficacy is one of the factors associated with low coverage of exclusive breastfeeding, while a husband’s support is known to positively influence a mother’s breastfeeding self-efficacy. This study examined the correlation between husband’s support and Breastfeeding Self-efficacy (BSE) in providing exclusive breastfeeding among mothers in the working area of the Community Health Center (Puskesmas) of Banda Raya in Banda Aceh city. This study was a quantitative study with a cross-sectional design. The population of this study includes 243 mothers who have children aged 6 months or less. The sampling was performed through stratified random sampling which resulted 78 respondents. Husband support and Breastfeeding Self-efficacy Scale- Short From (BSES-SF) questionnaires were used as the research instruments. The data were analyzed using bivariate and analysis Chi-Square test. The result showed a correlation between husband support (p-value 0,01), informational support (p-value 0,03), appraisal support (p-value 0,01), emotional support (p-value 0,03) and instrumental support (p-value 0,04) with BSE. The Health Community Center is urged to provide mothers with more information regarding the benefits of exclusive breastfeeding to ensure the success of optimum breastfeeding practices and to encourage mothers to take part in counseling about exclusive breastfeeding during antenatal care.